Endoscopic stenting for malignant gastric outlet obstruction: focusing on comparison of endoscopic stenting and surgical gastrojejunostomy - Sun Gyo Lim; Chan Gyoo Kim (Korean Society of Gastrointestinal Endoscopy, 2024)
Malignant gastric outlet obstruction (GOO) is a condition characterized by blockage or narrowing where the stomach empties its contents into the small intestine due to primary malignant tumors or metastatic diseases. This condition leads to various symptoms such as nausea, vomiting, abdominal pain, and weight loss. To manage malignant GOO, different treatment options have been employed, including surgical gastrojejunostomy (SGJ), gastroduodenal stenting (GDS) using self-expandable metallic stent (SEMS), and endoscopic ultrasound-guided gastrojejunostomy (EUS-GJ). This review focuses on comparing the clinical outcomes of endoscopic stenting (GDS and EUS-GJ) with SGJ for malignant GOO. Studies have shown that GDS with SEMS provides comparable clinical outcomes and safety for the palliation of obstructive symptoms. The choice between covered and uncovered SEMS remains controversial, as different studies have reported varying results. EUS-GJ, performed via endoscopic ultrasound guidance, has shown promising efficacy and safety in managing malignant GOO, but further studies are needed to establish it as the primary treatment option. Comparative analyses suggest that GDS has higher recurrence and reintervention rates compared to EUS-GJ and SGJ, with similar overall procedural complications. However, bleeding rates were lower with GDS than with SGJ. Randomized controlled trials are required to determine the optimal treatment approach for malignant GOO.